2022
DOI: 10.35568/abdimas.v4i2.1044
|View full text |Cite
|
Sign up to set email alerts
|

Empowering Women as Waste Bank Activists in South Tangerang City

Abstract: Garbage is one of the problems in the city of South Tangerang (Tangsel). Tangsel produces approximately 880 tons of waste every day. The increase in population has an impact on increasing the volume of waste from households. One of the methods used by the Tangsel city government to reduce waste is through the waste bank program since 2012 a total of 208 Waste Banks have been formed, however, only 50 percent are active. By looking at these conditions, there needs to be efforts to empower women in reactivating w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The results of the Chi Square test on the relationship between diet and hypertension incidence in the elderly in Paya Bujok Village. 20 This study was also reinforced by the results of another study conducted by Andriyani (2020), which showed that the elderly who had the habit of eating salty foods had a higher hypertensive status with a percentage of 62.2% and the subjects who did not have the habit of eating salty foods was only 37.8%. The results of the stusy showed a significant relationship between the habit of eating salty foods and hypertension status in the elderly at RSU Tangerang Selatan.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The results of the Chi Square test on the relationship between diet and hypertension incidence in the elderly in Paya Bujok Village. 20 This study was also reinforced by the results of another study conducted by Andriyani (2020), which showed that the elderly who had the habit of eating salty foods had a higher hypertensive status with a percentage of 62.2% and the subjects who did not have the habit of eating salty foods was only 37.8%. The results of the stusy showed a significant relationship between the habit of eating salty foods and hypertension status in the elderly at RSU Tangerang Selatan.…”
Section: Discussionmentioning
confidence: 68%
“…The results of the stusy showed a significant relationship between the habit of eating salty foods and hypertension status in the elderly at RSU Tangerang Selatan. 21 The results of this study showed that the elderly who had lack of physical activity were having 5.52 times greater chance to have hypertension compared to the elderly who had enough physical activities. The results of this study showed that the subjects had lack of physical activity such as walking, making crafts, dressing up, washing clothes, cleaning the environment, cleaning the bathroom, cleaning the trash can, and caring for others that can cause an increase in blood pressure.…”
Section: Discussionmentioning
confidence: 72%